MEDIA REPRESENTATION OF “BIPA” IN INDONESIAN NEWSPAPERS: A CORPUS-ASSISTED DISCOURSE STUDY - Aulia Noor Eliza; Fatikhatur Rizqya; Mohammad Ilham Yasin (JR-ELT (Journal of Research in English Language Teaching), 2026)
Bahasa Indonesia for Foreign Speakers (BIPA) has become an increasingly important component of Indonesia’s cultural diplomacy, particularly through the expansion of language-teaching programs abroad. As public discourse shapes perceptions of language promotion, media coverage plays an important role in framing how BIPA, its teachers, and its international learners are represented. This study examines the representation of BIPA in Indonesian newspapers using a Corpus-Assisted Discourse Studies (CADS) approach, focusing on keywords, collocation, and concordance patterns surrounding terms such as “BIPA” and “pengajar BIPA”. The analysis shows that BIPA is predominantly linked to discourses of cultural diplomacy, language promotion, international cooperation, and Indonesia’s global image, which indicate a strong framing of the program as a soft-power strategy. In contrast, structural challenges such as insufficient funding, limited teacher training, and institutional disparities appear far less frequently. Media reporting tends to foreground success stories, expansion efforts, and Indonesia’s cultural appeal, while giving limited attention to pedagogical issues, learner diversity, and long-term program sustainability. Overall, the findings suggest that Indonesian media coverage prioritizes promotional and nation-branding perspectives over critical or structural considerations. The study highlights the need for more balanced reporting that acknowledges both achievements and challenges, supporting a comprehensive understanding of BIPA’s role in cultural diplomacy and informing future policy development.